2017
DOI: 10.1007/s00431-017-3007-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal nonresponsive feeding practice and child’s eating behavior and weight status: children aged 1 to 6 years

Abstract: The findings provide strong evidence for the correlation between NRFR and CEB, and this indicates that prevention and intervention of unhealthy weight should start in early life. However, further research is necessary to gain an understanding of the impact of NRFP on CEB and weight. What is known: • Responsive feeding practice is crucial to the formation of eating behavior, and poor practice is associated with the current epidemics of childhood obesity and underweight. What is new: • The findings provide a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Children and adolescents who were breastfed for a shorter duration and those who were more physically active tended to prefer nuts/dried fruits/vegetables and drink artificially sweetened beverages. Our results add to the evidence that maternal feeding practices [41], food choice motives [42] and parents' characteristics, especially fathers' smoking status, play a crucial role in shaping food preference and consumption habit as well as healthy eating behaviors among children and adolescents in China.…”
Section: Discussionsupporting
confidence: 64%
“…Children and adolescents who were breastfed for a shorter duration and those who were more physically active tended to prefer nuts/dried fruits/vegetables and drink artificially sweetened beverages. Our results add to the evidence that maternal feeding practices [41], food choice motives [42] and parents' characteristics, especially fathers' smoking status, play a crucial role in shaping food preference and consumption habit as well as healthy eating behaviors among children and adolescents in China.…”
Section: Discussionsupporting
confidence: 64%
“…Among these risk factors, caregivers’ feeding practices have been shown to play an important role [ 8 , 9 , 10 , 11 ]. There are two types of feeding practices: non-responsive and responsive feeding [ 12 , 13 , 14 ]. Non-responsive feeding practices (also known as coercive control), such as forcing to eat, restricting food, and using food as a reward [ 15 ], have been widely studied and raised crucial concerns owing to their close links with childhood obesity [ 8 , 9 , 10 , 11 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides nutritional knowledge, other factors affect the nutritional status of children. Moreover, the level of parents' education has been proven to affect children's weight [7,[12][13][14]. Several studies showed the effectiveness of parental nutritional education in improving their children's health [15][16][17].…”
Section: Introductionmentioning
confidence: 99%